The Thracian Hero on the Danube: New Interpretation of an Inscription from Diana - Grbić, Dragana (Balcanica - Annual of the Institute for Balkan Studies, 2013)
The paper looks at some aspects of the Thracian Hero cult on the Danube frontier of Upper Moesia inspired by a reinterpretation of a Latin votive inscription from Diana, which, as the paper proposes, was dedicated to Deo Totovitioni. Based on epigraphic analogies, the paper puts forth the view that it was a dedication to the Thracian Hero, since it is in the context of this particular cult that the epithet Totovitio has been attested in various variants (Toto-viti- / Toto-bisi- / Toto-ithi-).